Aproximaciones históricas al joropo de espectáculo a partir de diálogos con maestros de la tradición en los llanos orientales - Pinzón Tamayo, Juan Esteban (Universidad Antonio Nariño, 2024)
The purpose of this degree project is to interpret information that allows the reader to understand the milestones and circumstances that gave rise to the "joropo espectáculo" (spectacle joropo). This is carried out through various data collection techniques. The first involves a review of theoretical and practical records that place the context of the topic to be addressed, and the second involves conducting interviews with teachers, knowledgeable individuals, practitioners, and/or bearers of the llanera tradition. These interviews take place in Bogotá or via the Meet platform, featuring prominent figures such as Gustavo Rodríguez (Villavicencio – Meta), Astrid Arenas (Tame – Arauca), Álvaro Rico (Tame – Arauca), and Marcela Hernández (Villavicencio – Meta). These experts were selected for their extensive knowledge and vast experience in the practice, promotion, and teaching of joropo, ensuring an enriching perspective for the research